Psychiatric comorbidity, addiction profile and desire for treatment in substance using adolescents: çematem data - Kuygun Karcı, Canan; Arıcı Gürbüz, Asiye; Akkuş Özdemir, Fatma; Altun Varmış, Dilek; Yolga Tahiroğlu, Ayşegül (Journal of Dependence, 2022)
Objective: Substance use among adolescents continues to be an important problem in our country as in the rest of the world. The aim of this study was to examine the characteristics of substance use in adolescents, psychiatric diagnoses, addiction profile, and treatment eagerness. Method: Fifty adolescents who applied to ÇEMATEM outpatient clinic were included in the study. For the psychiatric diagnoses of adolescents, affective disorders and schizophrenia interview schedule for school-age children-present and lifetime DSM-5 (K-SADS-PL-DSM-5-T) was used. For data related to substance use, the addiction profile index adolescent form (BAPI-E), DSM-5 Level-2 substance use scale and the State of Change Readiness and Treatment Eagerness Scale (SOCRATES) were used. Results: 39 of the adolescents included in the study were boys (78%), 11 (22%) girls, with an average age of 16.42±0.785. The most common comorbid psychiatric diagnoses were conduct disorder (70%), ADHD (38%) and depression (10%). All of the adolescents were using cigarettes (100%), 72% cannabis, 56% alcohol, 34% methamphetamine and 26% ecstasy. 90% of the adolescents stated that they started using substances through their friends. The substance was found positive in the urine test of 11 adolescents. It was observed that 68% of the adolescents who used substances did not attend school and reported more severe substance cravings compared to the adolescents who continued to school. It was found that as the age and the severity of addiction increased, the change readiness and treatment eagerness increased. Conclusion: The prevalence of school dropout, psychiatric comorbidity and substance-using friends among adolescents with substance use is supported by our study findings. For this reason, it should be aimed to prevent the initiation of substance use and to increase the willingness of adolescents to quit and seek treatment with appropriate interventions to risky groups.